Development of cobalt-doped zinc oxide photocatalyst nanoparticles for removal of nitrobenzene - Gidado, Liman Muhammad (2015)
The increasing rise of world population and rapid industrial development across the globe is not without problem, especially in terms of availability of potable drinking water. The photocatalytic oxidation of zinc oxide, ZnO, under UV irradiation on organic pollutants in water is well establish and nitrobenzene, NB, has been classified under persistent organic pollutants and reported as being carcinogenic. In this study, ZnO catalyst was synthesized via sol-gel and, for the first time, via combination of solgel and hydrothermal method, in the presence of ethylene and polyethylene glycol surfactants. The resulting powder was calcined at different temperatures (400, 500, 600oC) and for a different calcination periods (2, 4, 6 hours). The prepared samples were characterized using X-ray Diffraction (XRD, Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM), Surface Area Measurement (BET method), Diffuse Reflectance Spectroscopy (DRS), X-ray Florescence (XRF) and Electron Diffraction Spectroscopy (EDS). All ZnO samples were spherical with hexagonal structure and particle size ranges from 16 to 96 nm. The variation in surfactants, calcination temperature and calcination time have no significant effect on the properties of ZnO. The photocatalytic activity of the prepared ZnO was evaluated by degradation of NB, under 2h of UV light irradiation. ZnO prepared by a combined sol-gel and hydrothermal method, exhibits the highest photocatalytic activity (75% of NB removal). This is attributed to high surface area and small particle size. In order to enhance its photoactivity, the ZnO catalyst was doped with various percentage of cobalt, Co. The addition of Co onto ZnO did not change the morphology of the catalyst. There was no remarkable change in the band gap (3.20 eV for the 0.5% Co-doped ZnO and 3.22 eV for the undoped ZnO) but an increased in the surface area (12.6 m2/g for undoped ZnO to 17.6 m2/g for the 0.5% Co-doped ZnO) was observed. The photocatalytic activity of Co-doped ZnO catalysts in degradation of NB under UV light irradiation is 86% which is higher than that of ZnO (SGHP). The effects of catalyst mass, NB concentration as well as the solution pH were examined using the Co-doped ZnO catalyst, SP2. The best conditions for degrading NB were 0.75 g catalyst loading, 20 ppm NB and at a solution pH of 7. Under these conditions and for a 2 hours irradiation time, SP2 removed 86% and 83% of NB under UV light and visible light irradiation, respectively. The ability of the SP2 catalyst to effect 83% NB removal under visible light irradiation is a landmark achievement because greater part of solar radiation consists of visible light. The degradation of NB follows first-order reaction with a rate constant k1 equals to 2.16 x 10-2 mgL-1 min-1 and a half-life period of 32 min. Chemical Oxygen Demand (COD) and Total Organic Carbon (TOC) analyses, after a 2 hour photodegradation period, showed a 79% and 66% removal of NB, respectively, indicating a substantial degradation of the pollutant. The SP2 catalyst showed no significant loss in photoactivity after 5 cycles of photodegradation reaction suggesting that many more cycles are possible before reaching 50% drop in the photoactivity; a pointer to its reusability.